Cotejos da ciência: o projeto norte americano R.I.T.A no nordeste brasileiro (Brasil e EUA, anos 1960) - Gomes, Assis Daniel (2020)
In this work, we intend to analyze the relations between Brazil and the USA based on the RITA Project, implemented in the Brazilian Northeast in the 1960s. For this, we walked through the Social History of Science, Technique and Labor to also consider the scientific studies carried out in favor of industrialization of some regions, for example, Cariri Ceará. To that end, we realize that local political projects and Universities have contributed to consolidating this purpose, as well as signing the agreement with North American Universities, through the Alliance for Progress; thus generating it effectively. Analyzing the desires that moved internal and external capital, the process of implantation and expansion of its manufacturing projects, clarifies us about the place assumed by Latin America, particularly Brazil, in the Cold War years, as well as providing us with indications for understand the role assumed by North American cultural imperialism and its diplomatic policy in the military coups that plagued the Americas since 1960. In short, to think, RITA was to walk through the “between-places” and the border speeches that hung according to the wind that came from their international relations. This particularity metamorphosed after the Civil-Military coup of 1964, whose dependence on North American capital was more firmly sealed.